The Revision of Macroeconomic Indicators in EU-28 on the Example of Gross National Income - Perkov, Josipa; Mikulandra Volić, Ivona; Lastavec, Marijana (Oeconomica Jadertina, 2017)
The largest part of the EU budget revenue, about 69%, comes from payments based on national income and expressed through the gross national income, making this indicator one of the most important macroeconomic indicators, and it is therefore important to ensure that it is equally measured together with other important economic indicators in all member countries. A major challenge for national statistical institutes is to link international and national requirements for data delivery, an issue additionally complicated by the fact that macro-level indicators aimed at implementing EU policies do not necessarily help decision making at national and local levels. In order to meet the requirements for the comparability of data, the Republic of Croatia must apply the same research methodology applied by the European Statistical System, while considering that the official Statistics of the Republic of Croatia even before the accession to the European Union had to initiate the necessary coordination and alignment with the European Statistical System methodologies and is still evaluating its conformity and adapting to the European system. Through the review of literature and available statistical reports this paper concludes that for the successful financing and thus the functioning of the European Union, it is important to further and continuously align the gross national income within the national macroeconomic statistics of the member states and the European Statistical System.